Ulasan Digital Wisata sebagai Basis Strategi Komunikasi Destinasi: Kajian Linguistik Korpus dan Analisis Wacana Kritis untuk Pengembangan Program "Merasakan Nglanggeran" - Shella Gherina Saptiany; Dyan Triana Putra; Nina Mistriani (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This article examines digital tourism reviews as primary data sources for understanding tourist experiences and community-based destination image formation. The study aims to formulate a conceptual framework for developing the "Merasakan Nglanggeran" program through the integration of Corpus Linguistics and Critical Discourse Analysis (CDA). A systematic literature review method was employed, focusing on publications from the past ten years addressing digital tourism reviews, corpus linguistics, critical discourse analysis, and community-based tourism. The findings reveal that digital tourism reviews are dominated by positive evaluative lexicon, repetitive narrative structures, and strong destination representations in terms of experience, service quality, and authenticity. The combined corpus-CDA approach proves effective in reading both linguistic patterns and underlying ideologies in tourism review texts. The study concludes that community-based digital narrative management has the potential to strengthen destination image, expand digital visibility, and support sustainable tourism. Practical implications are articulated through the "Merasakan Nglanggeran" program framework, oriented toward authenticity, community participation, and sustainability.